Analisis Tingkat Kesulitan Soal Pemecahan Masalah Dalam Buku Siswa Pelajaran Matematika SMP Kelas VIII Kurikulum 2013 - Mulyaningsih, Wahyu Mei, Idris Harta, M.A., Ph.D (2017)
This study aims to analyze and describe the level of difficulty of problem solving items mathematics in terms of the type of problem, the type of number, type of operation, the number of operations, the number of questions, the adequacy of the data and the similarity with the previous problem. This study uses qualitative research. The object of this study is the mathematics textbook for eight-grade of curriculum 2013 published by the Ministry of Education and Culture. Data accumulation techniques by determine of problem solving items in student textbooks. The data are analyzed using workflow stage data reduction, data presentation, and conclusion. The results showed: 1) There are 297 problem solving or approximately 23,35% of the 1.272 items; 2) Types of problems metter solving 80,81% dominant non-routine; 3) Types the number of dominant numbers count with of 63,39%; 4) Types of operations used multiplication with a of 28,93%; 5) Many operations more than one operation (>0) 83,16%; 6) Many of the questions used 71,72% have one question; 7) The adequacy of the complete data 96,63%; 8) Resemblance is a matter not similar to the previous of 76,77%. So about the problem solving is categorized having medium difficulty level task.